FROM INFORMATION PROCESSES TO COGNITIVE - Lokyan, Arsen; Allakhverdov, Victor; Aghuzumtsyan, Ruben (Modern Psychology, 2023)
The article is devoted to theoretical problems of the development of psychological science. A new scientific direction-cognitive psychology appeared based on the criticism of behaviorism, the development of which was facilitated by the advent of computers.The approaches of different scientists for understanding and describing the psychological component of a person are discussed and analyzed. The importance of the less studied categories such as consciousness, unconsciousness, intuition, etc. is emphasized in the article. The ways of development of theoretical and experimental psychology are discussed from the positions of cognitive psychology, the main model of which was: perception, processing and decision making by the human brain which is connected with the development of computer technology and the programming process. Behavioral psychology was replaced by informational psychology. At the same time, the rapidly developing and practical orientation of the new approach to knowledge and study of the human psyche has faced certain limitations. The limitations mentioned in article have deeper roots. Since the establishment of psychology as a scientific field, the human being, his psychological component and activity have been considered as the main principles. Different scientists of various times discussed in detail the essence of human psyche: activity, behavior in various situations, emotional and volitional manifestations. Such an excursion made it possible in understanding the nature of the limitations for the development of psychological science and tries to discuss the ways of overcoming them. One of the solutions is considered a more systematic and deep research of psychophysiological mechanisms of human brain activity due to the development of modern opportunities.Another way which is based on the integration of various sciences (for example, neurobiology, etc.) is a detailed study of various psychophysiological characteristics of a person. The approach makes possible to find answers to questions of such problems as consciousness, subconsciousness, intuition, creativity.
Keywords: behaviorism; cognitive psychology; informatization; psychological limitations and ways to overcome them